Relapse patterns in early‐PET negative, limited‐stage Hodgkin lymphoma (HL) after ABVD with or without radiotherapy–a joint analysis of EORTC/LYSA/FIL H10 and NCRI RAPID trials. (21st December 2022) - Fiaccadori, Valeria; Neven, Anouk; Fortpied, Catherine; Aurer, Igor; Andre, Marc; Federico, Massimo; Counsell, Nicholas; Phillips, Elizabeth H.; Clifton‐Hadley, Laura; Barrington, Sally F.; Illidge, Timothy; Radford, John; et al.
Summary: In the H10 and RAPID randomised trials, chemotherapy+radiotherapy (combined modalities treatment, CMT) was compared with chemotherapy (C) in limited‐stage Hodgkin lymphoma (HL), with negative early positron emission tomography (ePETneg). We analysed patterns of relapses in the H10 trial, validated findings in the RAPID trial and performed a combined analysis stratified by trial. The impact of radiotherapy (RT) on risk of relapse was studied using adjusted Cox models, with time‐varying effects. In H10, 1, 059 ePETneg patients were included (465 European Organisation for Research and Treatment of Cancer (EORTC) favourable [F], 594 unfavourable [U]). Among the F patients, 2/227 (1%) relapsed after CMT, 30/238 (13%) after C: of these relapses, 21/30 (70%) occurred in less than 2 years and 25/30 (83%) affected originally involved areas. Among the U group, 16/292 (5%) relapsed after CMT: 8/16 (50%) in less than 2 years, 11/16 (69%) in originally involved areas. After C 30/302 (10%) relapsed: 27/30 (90%) in less than 2 years, and 26/30 (87%) in originally involved areas. Similar results were observed in 419 ePETneg RAPID patients (241 F, 128 U, 50 unclassified): among F patients, 6/118 (5%) relapsed after CMT; 13/123 (11%) after C: 11/13 (85%) in less than 2 years and 11/13 (85%) affecting originally involved areas. In U patients, 3/65 (5%) relapsed after CMT and 5/63 (8%) after C. In both trials, omitting RT in ePETneg HL resulted in more early relapses, mainly affecting originally involved areas. RT significantly reduced risk of early relapses in the combined stratified analysis.